ASSOCIATION NOTES. - Austin, E. Burl (The Accounting Review, 1958)
This article presents information regarding the activities of several universities and colleges of Accounting. In the Claremont Men's College, George Gibbs has been elected to the Board of Examiners of the American Institute of Certified Public Accountants (CPAs) for a term of three years. Gibbs continues his membership on the California State Board of Accountancy. In Northwestern University, Erwin E. Nemmers, formerly of the University of Wisconsin, has been appointed associate professor in the Graduate School of Business Administration. The members of the accounting department met with partners and managers of Arthur Andersen & Co. at a dinner meeting in January 1958, to discuss matters of common interest to educators and practitioners. In the Long Island University-C. W. Post College, Charles H. Zwicker has been appointed lecturer in accounting. The college is now for the first time offering a major in accounting. In the New York University, Bruce Futhey has been appointed to membership on the committees on Education-Personnel and Governmental Accounting of the New York Society of CPAs.